The Federal Reserve response to 9-11 - Elias, Jaan; Rosenthal, Jean; English, William B. (London : Yale School of Management, 2020)
The attacks on New York City and the Pentagon in Washington, DC, on September 11, 2001, shocked the nation and the world. Hijacked passenger jets crashed into the Twin Towers of the World Trade Center in Manhattan, causing the death of 3,000 people and the destruction of multiple buildings and communications infrastructure. The attacks crippled the nerve center of the U.S. financial system. Information flow among banks, traders in multiple markets, and regulators was interrupted.The disruptions particularly challenged the Federal Reserve, the central bank of the United States. When the attacks had begun, Roger Ferguson, Vice Chair of the Fed's Board of Governors, was the only member of the Board of Governor reachable by phone to make the immediate decisions facing the organization. Throughout that Tuesday morning and the rest of the week he led the Fed through one of its most challenging periods.
Orginally Published InElias, J., Rosenthal, J., & English, W.B. (2020). The Federal Reserve Response to 9-11. 20-029. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ferguson, Roger Walton, -- 1951- -- Case studies; Board of Governors of the Federal Reserve System (U.S.) -- Case studies; United States. -- Federal Reserve Board -- Case studies; September 11 Terrorist Attacks, 2001 -- Economic aspects -- Case studies